2014 13th International Conference on Control Automation Robotics &Amp; Vision (ICARCV) 2014
DOI: 10.1109/icarcv.2014.7064437
|View full text |Cite
|
Sign up to set email alerts
|

Image segmentation based on histogram of depth and an application in driver distraction detection

Abstract: Abstract-This study proposes an approach to segment human object from a depth image based on histogram of depth values. The region of interest is first extracted based on a predefined threshold for histogram regions. A region growing process is then employed to separate multiple human bodies with the same depth interval. Our contribution is the identification of an adaptive growth threshold based on the detected histogram region. To demonstrate the effectiveness of the proposed method, an application in driver… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In robotic applications, many vision-based approaches have been proposed to deal with robotic color tracking and image segmentation 31,43,44,57 and employed to solve the defect detection problem. [45][46][47] To be applied in a fully automatic process, the proposed approach must be able to handle the input data with limited supervision and manual adjustment.In this work, a hybrid method is proposed to solve the mentioned problem by combining our automatic peak detection algorithm with image stitching and 3D registration.…”
Section: Steel Crack Detectionmentioning
confidence: 99%
“…In robotic applications, many vision-based approaches have been proposed to deal with robotic color tracking and image segmentation 31,43,44,57 and employed to solve the defect detection problem. [45][46][47] To be applied in a fully automatic process, the proposed approach must be able to handle the input data with limited supervision and manual adjustment.In this work, a hybrid method is proposed to solve the mentioned problem by combining our automatic peak detection algorithm with image stitching and 3D registration.…”
Section: Steel Crack Detectionmentioning
confidence: 99%
“…They introduce and solve the problem of Byzantine fault tolerant distributed quickest change detection in both continuous and discrete-time setups. More reviews could be found in [17][18][19][20][21][22][23][24][25].…”
Section: Literature Review and Analysismentioning
confidence: 99%
“…Compared to traditional methods, the CNN-based crack detection framework does not require the pre-extraction and calculation of features [32]. Moreover, CNN is based on automatic learning of crack features and does not require format conversion of input images [33]. Furthermore, the CNN-based crack detection architecture displays higher accuracy than the traditional methods [34][35][36].…”
Section: Introductionmentioning
confidence: 99%